It’s Never Too Early or Too Late—End the Epidemic of Alzheimer’s by Preventing or Reversing Causation From Pre-birth to Death - Trempe, Clement L.; Lewis, Thomas J. (Frontiers in Aging Neuroscience, 2018)
The path to sporadic Alzheimer’s is a tragic journey beginning prior to birth and ending in the most dreaded disease of society. Along the disease path are a myriad of clues that portend AD, many of which are complaints of seemingly unrelated conditions from chronic migraines, mood disorders, eye diseases, metabolic syndromes, periodontal diseases, hormonal, and autoimmune diseases. Properly treating, not just managing, these diseases, prior to onset of dementia, may significantly reduce dementia incidences. Current high levels of health complaints reflect a state of generalized poor health and compromised immunity. During the mid-Victorian era, people were long-lived yet healthy, suffering from chronic diseases at one tenth the rate of peoples today. It’s our poor health, at any age, that increases susceptibility to chronic diseases and Alzheimer’s. Infection is involved in many cases of Alzheimer’s and other neurodegenerative diseases but is also implicated in many chronic conditions. Scientists looking for causation recognize that Alzheimer’ is multifactorial and systemic – not “brain only.” To slow, stop, and reverse the AD epidemic, identification and reversal of causal factors must occur across the entire life spectrum of humans. This approach simply gives consideration to enhancing immune status of our bodies and brain, and controlling inflammation and infection, throughout the entire age spectrum. Infection is a causal factor, but the root cause is multi-factorial and immune health related. Pasteur stated it best when acknowledging the work of Bernard in 19th Century France, “The seed is nothing, the soil is everything.”